Phytochemical Analysis and Biological Activities of Different Extracts of Walnut (Juglans regia Linn.) Kernels - Das, Nabin; Tandukar, Pooja; Niraula, Muna; Gautam, Daman Raj; Pathak, Ishwor (Journal of Nepal Chemical Society, 2024)
The walnut tree (Juglans regia Linn.) is a valuable medicinal plant. Almost all parts of this plant have significant nutritional and curative properties. The walnut fruit has been claimed to possess antioxidant, anti-inflammatory, anti-hypertensive, antimicrobial properties and high nutritional value. The present work is focused on the phytochemical screening and study of antioxidant and antimicrobial properties of Juglans regia kernels extracted from four different solvents; methanol, ethyl acetate, chloroform, and hexane. The highest yield of extract was obtained with methanol. The phytochemical screening showed the presence of alkaloids, flavonoids, tannins, phenolic compounds, glycosides, terpenoids, quinones, reducing sugars, and saponins in methanol extract. The total phenolic content was higher in methanolic extract. Methanolic and chloroform extracts possessed more flavonoid content than ethyl acetate and hexane extracts. The DPPH radical scavenging assay showed that the IC50 value of methanolic extract was 78.77 μg/mL with TPC 67.65 mg GAE/g and TFC 391.00 mg QE/g. The IC50 value obtained for ethyl acetate extract was 135.28 μg/mL with TPC 36.56 mg GAE/g and TFC 212.00 mg QE/g. The IC50 value for chloroform extract was 313.72 μg/mL with TPC 13.08 mg GAE/g and TFC 393.73 mg QE/g. The IC50 value of hexane extract was 898.99 μg/mL with TPC 6.26 mg GAE/g and TFC 77.82 mg QE/g. Only methanolic extract showed the antimicrobial activity against Proteus vulgaris, Pseudomonas aeruginosa, and Staphylococcus aureus.